Co-administration of TiO2-nanowired DL-3-n-butylphthalide (DL-NBP) and mesenchymal stem cells enhanced neuroprotection in Parkinson's disease exacerbated by concussive head injury - Niu F.; Sharma A.; Wang Z.; Feng L.; Muresanu D.F.; Sahib S.; Tian Z.R.; Lafuente J.V.; Buzoianu A.D.; Castellani R.J.; Nozari A.; Patnaik R.; Wiklund L.; Sharma H.S. (My University, 2025)
DL-3-n-butylphthalide (DL-NBP) is a powerful antioxidant compound with profound neuroprotective effects in stroke and brain injury. However, its role in Parkinson's disease (PD) is not well known. Traumatic brain injury (TBI) is one of the key factors in precipitating PD like symptoms in civilians and particularly in military personnel. Thus, it would be interesting to explore the possible neuroprotective effects of NBP in PD following concussive head injury (CHI). In this chapter effect of nanowired delivery of NBP together with mesenchymal stem cells (MSCs) in PD with CHI is discussed based on our own investigations. It appears that CHI exacerbates PD pathophysiology in terms of p-tau, α-synuclein (ASNC) levels in the cerebrospinal fluid (CSF) and the loss of TH immunoreactivity in substantia niagra pars compacta (SNpc) and striatum (STr) along with dopamine (DA), dopamine decarboxylase (DOPAC). And homovanillic acid (HVA). Our observations are the first to show that a combination of NBP with MSCs when delivered using nanowired technology induces superior neuroprotective effects in PD brain pathology exacerbated by CHI, not reported earlier. © 2020 Elsevier B.V.